2009
DOI: 10.1021/jm900964r
|View full text |Cite
|
Sign up to set email alerts
|

7-Hydroxy-benzopyran-4-one Derivatives: A Novel Pharmacophore of Peroxisome Proliferator-Activated Receptor α and -γ (PPARα and γ) Dual Agonists

Abstract: Design, synthesis, and in vitro bioevaluation of a new class of potential dual PPARalpha and gamma agonists discovered through a structure-driven design paradigm are described. The 7-hydroxy-benzopyran-4-one moiety (includes flavones, flavanones, and isoflavones) is the key pharmacophore of these novel molecules, exhibiting similarity to the core structure of both fibrates and thiazolidinediones. New lead PPAR ligands were identified from "natraceuticals" and synthetic analogues. In total, 77 molecules, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…Matin et al have identified some synthetic flavanones, flavones and isoflavones as dual PPAR-α and -γ agonists [34], and further discovered some synthetic isoflavones that can activate three PPAR isoforms in vitro [35]. Here, for the first time, we identified BVC, a natural prenylated isoflavanone, as a potent pan-PPAR agonist.…”
Section: Discussionmentioning
confidence: 65%
“…Matin et al have identified some synthetic flavanones, flavones and isoflavones as dual PPAR-α and -γ agonists [34], and further discovered some synthetic isoflavones that can activate three PPAR isoforms in vitro [35]. Here, for the first time, we identified BVC, a natural prenylated isoflavanone, as a potent pan-PPAR agonist.…”
Section: Discussionmentioning
confidence: 65%
“…Recently, we have discovered synthetic analogues of isoflavones as novel templates for potential dual peroxisome proliferator-activated receptor (PPAR)-a and -g agonists. [16] During the course of our ongoing research, we envisioned for the first time, that isoflavones exhibit a potent flumazenil-insensitive positive modulation at human recombinant a 1 b 2 g 2L receptors expressed in Xenopus oocytes. The main goal of this communication is to report the in vitro GABA A activity of the isoflavones and to find correlations between the structure-driven design paradigm and the pharmacological activity.…”
mentioning
confidence: 99%
“…Bearing in mind the construction of the isoflavone core by a possible scalable synthesis, Felpin and co-workers [161] bed on a solution-phase Suzuki reaction using Pd(0)/C as heterogenous practical and inexpensive catalyst under ligand-free conditions, which was then used by other authors (Scheme 38) [162,163]. Beyond the excellent yields of cross-coupled products 114, the heterogeneous nature of the catalyst is extremely well suited for large-scale applications.…”
Section: Reactivity Of 3-halochromonesmentioning
confidence: 99%